1996
DOI: 10.1007/bf02101622
|View full text |Cite
|
Sign up to set email alerts
|

The Euler-Poincaré equations and double bracket dissipation

Abstract: This paper studies the perturbation of a Lie-Poisson (or, equivalently an Euler-Poincaré) system by a special dissipation term that has Brockett's double bracket form. We show that a formally unstable equilibrium of the unperturbed system becomes a spectrally and hence nonlinearly unstable equilibrium after the perturbation is added. We also investigate the geometry of this dissipation mechanism and its relation to Rayleigh dissipation functions. This work complements our earlier work Ratiu [1991, 1994]) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(182 citation statements)
references
References 64 publications
3
176
0
3
Order By: Relevance
“…In Marsden and Scheurle [1993b] it was shown that, for matrix groups, one could view the Euler-Poincaré equations via the reduction of Hamilton's variational principle from T G to g. The work of Bloch, Krishnaprasad, Marsden and Ratiu [1996] established the EulerPoincaré variational structure for general Lie groups.…”
Section: Reduction Theory: Historical Overview 31mentioning
confidence: 99%
See 1 more Smart Citation
“…In Marsden and Scheurle [1993b] it was shown that, for matrix groups, one could view the Euler-Poincaré equations via the reduction of Hamilton's variational principle from T G to g. The work of Bloch, Krishnaprasad, Marsden and Ratiu [1996] established the EulerPoincaré variational structure for general Lie groups.…”
Section: Reduction Theory: Historical Overview 31mentioning
confidence: 99%
“…Of course, in general, one of the great successes of reduction theory has been the advancement of stability theory, starting with Poincaré [1901aPoincaré [ ,b, 1910 and Arnold [1966a], and continuing with the energy-momentum method developed in Simo, Lewis and Marsden [1991]; see also Bloch, Krishnaprasad, Marsden and Ratiu [1996]. Apart from the many applications of standard semidirect product theory, we have already mentioned the significant application to underwater vehicle dynamics and stability by Leonard and Marsden [1997].…”
Section: Applications and Infinite Dimensional Problemsmentioning
confidence: 99%
“…(For a discussion with the links with the Lie-Poisson equations, see for example, Marsden and Ratiu [1994]; also see this reference and Bloch, Krishnaprasad, Marsden and Ratiu [1996] for the proof.) Theorem 2.4 Let G be a Lie group and L : T G → R a left invariant Lagrangian.…”
Section: The Euler-poincaré Equations and Variational Principlesmentioning
confidence: 99%
“…Symmetry plays a special role in variational principles. Not only does it lead to conservation laws of Noether, but the reduced variational principle for the Euler-Poincaré equations on a general Lie algebra induced by Hamilton's principle on the corresponding Lie group was only recently found (Marsden and Scheurle [1993b] and Bloch, Krishnaprasad, Marsden and Ratiu [1996]). In fluid mechanics, such variational principles were associated with "Lin constraints", but even here it was only with work such as Seliger and Whitham [1968] and Bretherton [1970] that the situation was clarified.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several scientists working in the field called "Geometric Mechanics", used the equations obtained by Poincaré (which they called "Euler-Poincaré equations") to solve various problems. Following a remark made by Poincaré at the end of his note, several authors observed that these equations become very simple when the Lagrangian L is such that its value L(v) at a vector v tangent to the configuration space at a point x, only depends on the element of the Lie algebra of vector fields which, at the point x, takes the value v. Modern authors sometimes call "Lagrangian reduction" [2,3,4,5,6,7,8,9,10,18] the use of that property to make easier the determination of motions of the system. Assumptions made in these recent papers and books seem to us very often more restrictive than those made by Poincaré himself; for example, several modern authors assume that the mechanical system under study has a Lie group as configuration space, and that its dynamics is described by a Lagrangian invariant under the lift to the tangent bundle of the action of this group on itself by translations either on the right or on the left.…”
Section: Introductionmentioning
confidence: 99%